Cría y manejo del cachorro del lobo ibérico (Canis lupus signatus) - Revuelta Rueda, Luis; Aceituno Arnold, Nicole; Rodriguez Ponga, Virginia; Nájera Muñoz, Fernando (Revista Complutense de Ciencias Veterinarias, 2008)
The Iberian wolf (Canis lupus signatus)is a wild animal well represented in zoological parks. This work exposes the performance protocols for a correct managing of the newborn of wolf during the artificial lactation, as well as for wean and his preventive medicine (vaccination and worm). Also take into account the influences of the human factor in their development and the most frequent pathologies than can be presented in the Iberian wolf in this age. In this work we employ different teat, depending on the age on the animals. We used artificial milk of domestic dog during the lactation and meat of different origin for there wean. The vaccines used to carry out the proposed preventive medicine protocol were commercial vaccines of domestic dog. The cubs of this work acquired, after six months, the physiological characteristics; weight, size, etc. waited. The protocols proposed in this work were considered valid for the breed of the cub of Iberian wolf in zoological parks.